Precise radiometric age establishes Yarrabubba, Western Australia, as Earth’s oldest recognised meteorite impact structure - Erickson, Timmons; Kirkland, Chris; Timms, Nick; Cavosie, Aaron; Davison, T.M. (NATURE PUBLISHING GROUP, 2020)
The ~70 km-diameter Yarrabubba impact structure in Western Australia is regarded as among Earth’s oldest, but has hitherto lacked precise age constraints. Here we present U–Pb ages for impact-driven shock-recrystallised accessory minerals. Shock-recrystallised monazite yields a precise impact age of 2229 ± 5 Ma, coeval with shock-reset zircon. This result establishes Yarrabubba as the oldest recognised meteorite impact structure on Earth, extending the terrestrial cratering record back >200 million years. The age of Yarrabubba coincides, within uncertainty, with temporal constraint for the youngest Palaeoproterozoic glacial deposits, the Rietfontein diamictite in South Africa. Numerical impact simulations indicate that a 70 km-diameter crater into a continental glacier could release between 8.7 × 1013 to 5.0 × 1015 kg of H2O vapour instantaneously into the atmosphere. These results provide new estimates of impact-produced H2O vapour abundances for models investigating termination of the Paleoproterozoic glaciations, and highlight the possible role of impact cratering in modifying Earth’s climate.